2017
DOI: 10.3892/mmr.2017.7082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial community composition and diversity in postoperative intracranial infection using high-throughput sequencing

Abstract: Intracranial infection is one of the most serious complications following neurosurgery. It is well acknowledged that bacteria and fungi are the main pathogens responsible for postoperative intracranial infection. However, the microbial community structure, including composition, abundance and diversity, in postoperative intracranial infection is not fully understood, which greatly compromises our understanding of the necessity and effectiveness of postoperative antibiotic treatment. The present study collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Postoperative nervous system infection is a common complication of neurosurgery and accounts for 0.8ā€“7% of intracranial infections [ 1 ]. The most common pathogens are Gram-negative Bacilli and Staphylococcus aureus , but the percentage of post-neurosurgical intracranial infections caused by Acinetobacter baumannii is still high at 15ā€“21.74% [ 2 , 3 ] with a high associated mortality rate ranging from 20 to 40% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative nervous system infection is a common complication of neurosurgery and accounts for 0.8ā€“7% of intracranial infections [ 1 ]. The most common pathogens are Gram-negative Bacilli and Staphylococcus aureus , but the percentage of post-neurosurgical intracranial infections caused by Acinetobacter baumannii is still high at 15ā€“21.74% [ 2 , 3 ] with a high associated mortality rate ranging from 20 to 40% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative infection rate after burr hole trephination is ranges from 1.1ā€“10%. 19 21) In this study, there was no reported infection in any cases.…”
Section: Discussionmentioning
confidence: 49%
“…High risk factors of neonatal PM. Studies have found that neonatal PM infection is mainly related to three ways ( 5 ). The first way is antepartum infection, which is mainly caused by maternal factors; if mothers are infected with bacteremia before delivery, the neonates may be infected through placental circulation.…”
Section: Discussionmentioning
confidence: 99%